The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art